Characterisation of transmission channel for wireless LAN and mobile systems - Ong, Jin Teong (2008)
Measurements of multipath delays for wireless LAN systems operating in the 2,5, and 18GHz bands were carried out in two different laboratories and in the foyer of the main Lecture Theatre of NTU.